ANALYSIS OF RAW MATERIAL INVENTORY CONTROL USING THE ECONOMIC ORDER QUANTITY METHOD IN THE TAHU TEMPE JAGOR TOLITOLI BUSINESS: ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EKQ) DI USAHA TAHU TEMPE JAGOR TOLITOLI - Sahria Sahria; Edi Yanto (International Journal of Economic Entrepreneurship and Business Management, 2024)
This study aims to find out and analyze the Control of Raw Material Inventory in the Tofu Tempeh Jagor Toli Business, This study uses a quantitative research design. Data sources are in the form of Primary and Secondary data, Primary data is data collected directly from the main source such as interviews and so on, and secondary data is the data of a research taken from existing sources in the form of evidence, records or historical reports that have been compiled or the recording process carried out by the party concerned. The data collection techniques used are observations, information or explanations expressed in numbers or in the form of numbers, then drawing conclusions and quantitative data in the form of questionnaire data are analyzed with quantitative data analysis techniques. Based on the results of the study and discussion, it was concluded that it can be known that the comparison of soybean raw material inventory between company policies and the use of the EOQ method can be known. Based on the results of the inventory cost analysis, it can be seen that the Company's calculation results for 2021 amounted to Rp.293,190 while according to EOQ amounted to Rp.206,983 so that with the implementation of EOQ, a savings of Rp.86,207 was obtained, then in 2022 the Company's value was obtained of Rp.315,840 according to the EOQ of Rp.221,524 a saving of 94,316 and in 2023 the Company's value was obtained of Rp.333,000 according to the EOQ of Rp.231,991 a saving of Rp.101,009. analysis can be said that with the implementation of EOQ, the company can obtain inventory cost savings.